Strategies for Increasing the Competence of Sharia Banking Students’ Career Interest in Sharia Financial Institutions - Annisari Annisari; Tuti Anggraini (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
Indonesia is a country with the largest Muslim population of 231,069,932 people based on data from the Indonesian ministry of religion. That figure is equal to 84.37% of Indonesia’s total population of 273,879,750 people. As home to 84.37% of the Muslim population, Indonesia has fantastic potential sharia in the business world. The development of the sharia business lately has been rapid. Many demand scholars who understand the world of sharia business has resulted in increased job opportunities. The availability of vacancies in Islamic financial institutions requires competent human resources or graduates in the fields of economics and Islamic banking. The purpose of this research is to analyze the strategy of increasing the competence of sharia banking students at UIN Sumatera Utara in the interest of a career in sharia financial institutions. The research uses a qualitative approach with a descriptive analysis method. Research techniques used are interview, observation, literature review, and documentation. The result showed that the informant has a high interest in a career in sharia financial institutions due to labor market considerations, the working environment, financial rewards/salaries, and religiosity. However, it is not in line with the dominance of human resources who have no sharia banking education background in these institutions. Thus, we need the right strategy to improve the competence of students in order to produce sharia graduates who are competent and ready to compete in the world of work financial rewards/salaries and religiosity. Therefore, we need the right strategy to improve the competence of students in order to produce sharia graduates who are competent and ready to compete in the world of work.